Função sexual e níveis de testosterona em mulheres hetero e homossexuais - SILVA, Caio Santos Alves da (Universidade Federal do Pará, 2019)
The evolutionary psychology has demonstrated that sex has functions beyond the reproduction having evolved for promoting the emotional proximity of the couple and increasing the degree of satisfaction with the partner. However, most studies have focused on explaining the sexuality of heterosexual couples, thus leaving a gap with regard about sexuality of homosexual women. Nowadays there are signs about differences in the quality of sex life of women heterosexual and homosexual, as well as it has been observed that homosexuals groups do not constitute a homogeneous entity, with differences in lifestyle, preferences, and hormone levels. This study aimed to investigate the quality of sexual life and differences in free testosterone levels in three groups of women: hetero, homosexuals femme and homosexuals butch using the instrument Female Sexual Function Index due to its ability to measure the domains of sexual function. Participated in this study 55 heterosexual women, 39 femme and 17 butch. As regards sexual practices, 64.7% of participants in the butch group would like to have five or more sexual intercourses per week, versus 46.2% in femme group and 34% in the hetero group, demonstrating that homosexual women have more sexual desire. Heterosexual women showed lower frequency of preliminary activities such “be masturbated by the partner”, where 35% practice more than once a month, while 59% of the femme groups and 41% of butch groups practice more than once a week. Similar results were found in “receiving oral sex from the partner”, where 41% of hetero reported practicing more than once a month, while 51% of femme and 35% of butch's practicing more than once a week. The FSFI score showed a significant difference between heterosexual women (28.44) and the femme (31.31) and butch groups (30.82). The analysis of the salivary testosterone showed that butch group has the highest concentration, reaching 99,2 pg/ml, followed by femme group, with 56.09 pg/ml and lastly the hetero with 43.3 pg/ml. Comparing the average testosterone there was a significant difference between the femme and butch groups (p <0.01) and between hetero and butch (p = 0.001). Among the hetero and femme groups there was no difference. Correlations were found between testosterone levels and domains of the FSFI. In the group heterosexual there was a correlation with the domain of satisfaction (r = 0.732, p = 0.01). No correlation was found in the femme group, in the butch group occurred a negative and strong correlation with the domain of lubrication (r = - 0.621, p = 0.41). The results show that homosexual women are less likely to have sexual dysfunction than heterossexual. Homosexual women invest more in behaviors generators of excitement and orgasms as kissing, fondling, genital stimulation and receptive oral sex compared to Hetero Couples. It is likely that investment in foreplay stimulation occurs because of a greater desire in homosexuals women to have emotional closeness to their partner, which may be different in a heterosexual relationship where the man possibly practice the relation prioritizing their own sexual satisfaction.